Avaliação da manutenção do torque durante abdução isométrica e do desempenho muscular durante abdução concêntrica e excêntrica em sujeitos com síndrome do impacto do ombro - Camargo, Paula Rezende (2010)
There is lack of studies with approach on the evaluation of torque steadiness in subjects with shoulder impingement, as well as studies evaluating the eccentric phase of elevation of the arm in these subjects. As such, the purpose of this study was to evaluate torque steadiness during isometric abduction and muscle performance during concentric and eccentric abduction of the shoulder in subjects with subacromial impingement syndrome (SIS) and healthy subjects. The SIS group consisted of 27 subjects (33.489.94 years) with unilateral SIS and it was divided into two groups: 1) SIS with the dominant involved side; 2) SIS with the nondominant involved side. The control group consisted of 23 healthy subjects (32.269.04 years). Peak torque and torque steadiness were measured during isometric abduction (80º in the scapular plane) of the shoulder. Standard deviation, coefficient of variation, stability time, median frequency, and relative power were measured from the steadiness trials. The target torque was 35% of peak torque. There were neither significant interactions between group and side (P > 0.05), nor were there significant main effects of group and side (P > 0.05) for all variables analyzed. Peak torque, total work and acceleration time were measured, bilaterally, during isokinetic concentric and eccentric abduction at 60°/s and 180°/s. No significant interactions were found between group and side (P>0.05), as well as no significant main effects of group and side (P>0.05) for all variables during concentric abduction of the shoulder at both tested speeds. During the eccentric contractions, lower total work (P<0.05) was demonstrated by the nondominant uninvolved side of SIS group at 60°/s, and by the uninvolved sides of the SIS groups at 180°/s compared to the dominant side of the controls. At 180°/s, the nondominant uninvolved side of the SIS group demonstrated slower acceleration time (P<0.05) compared to the dominant side of the control group, as well as the nondominant involved side of the SIS group compared to the nondominant side of the controls. The results of this study showed that steadiness is preserved by SIS during isometric abduction of the shoulder. No alterations were also shown in the measured parameters during concentric and eccentric phases of isokinetic abduction in subjects with SIS when compared to a control group. However, alterations may be observed in the contralateral side during the eccentric phase of abduction in subjects with unilateral conditions of SIS.